1978
DOI: 10.1002/1097-0142(197810)42:4<1834::aid-cncr2820420423>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of cerebellar hemangioblastoma

Abstract: Light and ultrastructural features of a cerebellar hemangioblastoma in a 56-year-old man are described in detail. The neoplasm was composed of three major cell types: endothelial cells, pericytes, and stromal cells. The endothelial cells lined the fenestrated vascular channels. The pericytes were ensheathed by their own basal lamina which separated them from the basal lamina covering the endothelium. The stromal cells contained, in addition to the conventional organelles, numerous membrane-bound lipid inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 40 publications
(4 reference statements)
0
22
0
Order By: Relevance
“…Among the stromal cells, Chaudry et al identified cells with transitional features among stromal cells, endothelial cells, and pericytes. They also found ultrastructural features characteristic for embryonic cells and concluded that stromal cells and vasoformative elements share ga common ancestry, most likely angioblastic lineage (38). Therefore, although a synopsis of previous ultrastructural studies is similarly as inconclusive as previous immunohistochemical studies, ultrastructural studies recognized embryonic characteristics in the stromal cells and variable phenotypes of differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…Among the stromal cells, Chaudry et al identified cells with transitional features among stromal cells, endothelial cells, and pericytes. They also found ultrastructural features characteristic for embryonic cells and concluded that stromal cells and vasoformative elements share ga common ancestry, most likely angioblastic lineage (38). Therefore, although a synopsis of previous ultrastructural studies is similarly as inconclusive as previous immunohistochemical studies, ultrastructural studies recognized embryonic characteristics in the stromal cells and variable phenotypes of differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…This high Lip peak in the tumor is compatible with the histological fi ndings: stromal cells in this tumor contain Lip. 6 Concerning the high Lip peak seen with proton MRS, it is also observed in other tumors, especially high-grade tumors such as high-grade gliomas, metastatic brain tumors, and anaplastic meningiomas. 7,8 Several authors have noted the necrotic component as the origin of the Lip peak in these tumors 9 but not in hemangioblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…CD10, EMA ) was useful for differential diagnosis of hemangioblastoma from metastatic renal cell carcinoma. Several electron microscopic studies have demonstrated the vascular origin of these cells 14,20 which is supported by the presence of WeibelPalade bodies 21 .…”
Section: Casesmentioning
confidence: 93%